The Relationship Between Hba1c Levels in Type 2 Diabetes Mellitus Patients and Clinical Manifestations of Diabetic Microangiopathy Neuropathy With The Incidence of Erectile Dysfunction - Pursetyo, Travesthi Dian; Ilmawan, Moh. Fathi; Yudadi, Redemptus; Risma, Risma (Green Publisher Indonesia, 2025)
Type 2 diabetes mellitus is a chronic disease that can lead to various complications. This study aims to analyze the relationship between HbA1c levels and the clinical manifestations of diabetic microangiopathy neuropathy with the incidence of erectile dysfunction in patients with type 2 diabetes mellitus. The objective is to understand the prevalence of the relationship between HbA1c levels, the clinical manifestations of diabetic microangiopathy neuropathy, and the occurrence of erectile dysfunction in patients with type 2 diabetes mellitus. This study used an observational analytical design with a cross-sectional approach. The sample consisted of 61 male patients who underwent examination at RSPAL dr. Ramelan Surabaya from July to September 2024. Data was collected through interviews using the International Index of Erectile Function (IIEF-5) questionnaire, along with secondary data on HbA1c levels and symptoms of diabetic neuropathy. Statistical analysis was performed using the Chi-Square test to identify relationships between the study variables. The results of the study showed a significant relationship between HbA1c levels and the incidence of erectile dysfunction. However, there was no significant relationship between the clinical manifestations of diabetic microangiopathy neuropathy and erectile dysfunction, as indicated by the Chi-Square test. The conclusions of this study are: first, there is a strong relationship between uncontrolled HbA1c levels and the incidence of erectile dysfunction, and second, although the clinical manifestations of diabetic microangiopathy neuropathy are common in patients with type 2 diabetes mellitus, no direct significant relationship was found between the clinical manifestations of diabetic microangiopathy neuropathy and erectile dysfunction.